An analysis of innovative and maintenance free active pre-stressed soil nail with reinforced grout hybrid anchor in the region of Rawang, Malaysia - Jamain M.F.; Muda M.A.; Beddu S.; Noor M.J.M.; Manan T.S.B.A.; Ahmad M. (Springer Science and Business Media Deutschland GmbH, 2023)
Concrete construction; Creep; Grouting; Mortar; Prestressing; Reinforcement; Soil mechanics; Creep behaviors; Creep displacement; Hybrid anchors; Pre-stressed; Pull-out; Reinforced-grout hybrid anchor; Soil behaviors; Soil nail systems; Soil nails; Tensile; Soils; anchor; creep; displacement; grout; reinforced concrete; soil mechanics; soil nailing; soil-structure interaction; tensile strength; Malaysia